Babesia, Theileria, Plasmodium and Hemoglobin - Daniel Sojka; Marie Jalovecká; Jan Perner (Microorganisms, 2022)
The Propagation of Plasmodium spp. and Babesia/Theileria spp. vertebrate blood stages relies on the mediated acquisition of nutrients available within the host’s red blood cell (RBC). The cellular processes of uptake, trafficking and metabolic processing of host RBC proteins are thus crucial for the intraerythrocytic development of these parasites. In contrast to malarial Plasmodia, the molecular mechanisms of uptake and processing of the major RBC cytoplasmic protein hemoglobin remain widely unexplored in intraerythrocytic Babesia/Theileria species. In the paper, we thus provide an updated comparison of the intraerythrocytic stage feeding mechanisms of these two distantly related groups of parasitic Apicomplexa. As the associated metabolic pathways including proteolytic degradation and networks facilitating heme homeostasis represent attractive targets for diverse antimalarials, and alterations in these pathways underpin several mechanisms of malaria drug resistance, our ambition is to highlight some fundamental differences resulting in different implications for parasite management with the potential for novel interventions against Babesia/Theileria infections.